REVIEW OF YASHTIMADHU ON MENTAL HEALTH W.S.R TO MEDHYA RASAYANA (AYUSHDHARA, 2019)
Ayurveda lays stress on various measures to be adopted in order to promote mental health and to prevent mental disorders through Sadvritta, Dincharya, Ritucharya, Vegavidharana and Rasayana. Yashtimadhu Churana (powder of Glycyrrhiza Glabra with milk) is one among four Medhyarasayana mentioned in Charak Chikitsa. Generally most of the Rasayana are micro-molecular nutrients having Balya, Medhya, Agnivardhaka, Ojovardhaka and Vayasthapana properties and had been also proven the pharmacological properties like immunomodulator, adaptogenic, anti-stress, anti-anxiety, anti-depressant, anti-oxidant and nutrient tonic. Mandukparni Swarasa (juice of Centella asiatica), Yashtimadhu Churana (powder of Glycyrrhiza Glabra with milk), Guduchi Swarasa (juice of Tinospora cordifolia) and Kalka (paste) of Shankhapushpi Moola and Phala (root-fruit of Convolvulus pluricaulis) are mentioned as Medhyarasayana. Rasayana nourishes each and every cell of the body and hence contributes to the integrity and replenishment of Saptadhatus. Also it helps in the promotion of memory and intelligence, provide immunity against disease and maintain optimum strength of body and mind.